Allogeneic stem cell transplantation as initial salvage for patients with acute myeloid leukemia refractory to high‐dose cytarabine‐based induction chemotherapy. Issue 4 (7th March 2014) - Jabbour, Elias; Daver, Naval; Champlin, Richard; Mathisen, Michael; Oran, Betul; Ciurea, Stefan; Khouri, Issa; Cornelison, A Megan; Ghanem, Hady; Cardenas‐ Turanzas, Marylou; Popat, Uday; Ravandi, Farhad; et al.
<x xml:space="preserve">Abstract</x> Outcomes of patients with acute myeloid leukemia (AML) who are refractory to high‐dose Cytarabine (HiDAC)‐based induction are dismal. Allogeneic hematopoietic stem cell transplantation (AHSCT) as initial salvage may be effective and potentially superior to conventional salvage chemotherapy. Eighteen percent (285 of 1597) of AML patients were primary refractory to HiDAC‐based regimens at the MD Anderson Cancer Center between 1995 and 2009. AHSCT was the initial salvage in 28 cases. These patients were compared against 149 patients who received salvage chemotherapy, but never received AHSCT. Patients receiving salvage chemotherapy were older, had higher bone marrow blasts percentage, and higher incidence of unfavorable cytogenetics (P < 0.001). Median time from induction to AHSCT was 76 days. Objective response was achieved in 23 of 28 patients (82%) undergoing AHSCT. The incidence of grade III/IV acute and chronic graft versus‐host‐disease was 11% and 29%, respectively. Median follow up for living patients is 80 months. Median overall survival (OS) was 15.7 months and 2.9 months for AHSCT and chemotherapy, respectively (P < 0.001); the 3‐year OS rates were 39% and 2%, respectively. ASHCT as initial salvage therapy was identified as an independent prognostic factor for survival in multivariate analysis (HR = 3.03; P < 0.001). Initial salvage therapy with AHSCT in patients with primary HiDAC refractory AML is feasible and may yield superior outcomes to salvage chemotherapy. Am. J. Hematol. 89:395–398, 2014. © 2013 Wiley Periodicals, Inc.